The Coherence of the Qur’anic text according to the Advanced Scholars of Interpretation: its tools and applications - Alhaj, Waleed (Jordan Journal of Islamic Studies, 2023)
At the beginning of this study, the researcher defined the concept of text, linguistically and idiomatically, and what is related to it, as a preliminary step toward entering the world of textual studies. Then the study presents the most prominent tools and means on which advanced interpreters, with their grammatical, rhetorical, or other backgrounds, relied in their text analyses of the Holy Qur'an. The research did not neglect the modern linking tools and their impact on creating coherence and cohesion between the parts of the text, so conjunction in its two types was studied: conjunction in sentences and conjunction in the story, in addition to studying deletion and context, and ending with the study of reference with its types: pronouns, indicative, and communicative. The research did not neglect the application of endoscopy to develop an Arabic textual theory that is compatible with the nature of our Arabic language and is not unique to it, desiring to serve the study of Arabic texts, especially the Holy Qur’an.